Neonatal inflammation and near-term white matter microstructure in infants born very preterm - Kathryn G. Anderson; Molly F. Lazarus; Lisa Bruckert; Rocio V. Poblaciones; Melissa Scala; Virginia A. Marchman; Heidi M. Feldman; Katherine E. Travis (Neuroimage: Reports, 2024)
Background: Severe neonatal inflammatory conditions in very preterm infants (VPT: <32 weeks gestational age, GA) are linked to adverse neurodevelopmental outcomes. Differences in white matter (WM) microstructure of the corpus callosum (CC) have been observed at age 6 in VPT children with a history of severe neonatal inflammation. The goal of this study was to determine whether these CC differences can be detected at term-equivalent age using diffusion MRI (dMRI), and whether neonatal inflammation is associated with altered WM in additional tracts implicated in the encephalopathy of prematurity. Methods: We conducted a retrospective study of VPT infants (n = 152) born at 22–32 weeks GA, classified based on the presence (I+, n = 80) or absence (I-, n = 72) of severe neonatal inflammatory conditions (bronchopulmonary dysplasia, necrotizing enterocolitis, or culture-positive sepsis). Analysis of covariance (ANCOVA) assessed group differences in near-term dMRI mean fractional anisotropy (FA) and mean diffusivity (MD) across seven segments of the CC and the anterior thalamic radiation, arcuate fasciculus, cingulum, corticospinal tract, inferior longitudinal fasciculus, superior cerebellar peduncle, and uncinate fasciculus. Due to imbalance of GA in the full sample, secondary ANCOVA analyses were performed in a GA-matched subset (n = 42) to further isolate the effect of inflammation. Results: FA was significantly lower in the I+ group compared to the I- group in the anterior frontal, posterior parietal, temporal, and occipital segments of the CC, and in the cingulum, inferior longitudinal fasciculus, and superior cerebellar peduncle. This general pattern persisted in the GA-matched subset, with significant differences in the anterior frontal and temporal CC segments. Conclusions: VPT infants with severe neonatal inflammation had lower FA in multiple white matter tracts, suggesting that inflammation-related alterations in WM development begin in the neonatal period. The observed differences detected using dMRI at term-equivalent age corroborate prior findings and may provide a window of opportunity for early identification of VPT infants at increased risk of poor neurodevelopmental outcomes.